Concrete frame structure of block 11 and block 12 of Academic Building for Faculty of Geoscience and Petroleum Engineering at University Teknologi Petronas Seri Iskandar Perak / Siti Fatin Najihah Samsul Bahari - Samsul Bahari, Siti Fatin Najihah (Universiti Teknologi MARA, Perak, 2018)
Concrete is the most important material to construct the building in construction. The main topic discussed in this report is related to the structure of the building based on project "The Proposed construction and completion of Block 11 and Block 12 of Academic Buildings for Faculty of Geosciences & Petroleum Engineering and TNB 33Kv Substation". The objectives of this report is to study the method of the beam, slab and column construction of the building from early to final stage of concrete and to determine the machinery and equipment used for the construction. It will focus on the construction of the structure frame such as beam, slab and column for the building. In conclusion, this report content all the element and material related to the construction of the beam, slab and column structure according to the drawing and specification given for company.